Ventilators and Ventilatory Modalities - Pavone, Martino; Verrillo, Elisabetta; Onofri, Alessandro; Caggiano, Serena; Cutrera, Renato (Frontiers in Pediatrics, 2020)
Non-invasive ventilation is increasingly used in children for acute and chronic clinical conditions characterized by the development of severe respiratory failure. Ventilators available for clinical practice have different levels of complexity and clinicians need to know in detail their characteristics, setting variables and performances. A wide range of ventilators is currently capable of delivering non-invasive ventilation. Based on their main characteristics, bi-level ventilators, intermediate ventilators, and intensive care ventilators can be distinguished. Simple or advanced continuous positive airway pressure devices are also available. Differences between ventilators may have implications on the development of asynchronies and air leaks and may favor discomfort and poor patient tolerance. Various volume-targeted (controlled) and pressure-targeted (controlled) modes are also available, even if when performing non-invasive ventilation the pressure-targeted (controlled) mode are preferable because guarantee more constant pressures and a better management of the air leaks. Pressure support ventilation represents the most used non-invasive ventilation mode, as it is most physiological one. The newest ventilators allow the clinicians to use the hybrid modes which combine the advantages of volume and pressure-targeted (controlled) ventilation while limiting their drawbacks. The use of in-built software help clinicians to optimize the ventilators setting as well as check objectively the patient adherence to the treatment. The choice of the ventilator and the clinician proficiency are crucial steps to improve the chance of a successful non-invasive ventilation program.